ASSESSING OCCUPATIONAL HEALTH RISKS ASSOCIATED WITH MEDICAL WASTE MANAGEMENT AMONG HEALTHCARE WORKERS IN DISTRICT HOSPITALS OF RWANDA - Philbert Iradukunda (Journal of Social Political Sciences, 2026)
Healthcare waste presents a persistent threat to occupational health, particularly in low- and middle-income countries where waste management systems often face resource and enforcement challenges. In Rwanda, despite national policy frameworks, healthcare workers remain vulnerable to these hazards. This study evaluates the occupational health risks associated with healthcare waste in Rwanda’s district hospitals and proposes strategies to strengthen worker protection. A secondary data review was undertaken, drawing on peer-reviewed literature, WHO guidelines, and Rwanda’s National Healthcare Waste Management Plan 2021–2025. Data were thematically analyzed to identify predominant risks, systemic gaps, and opportunities for improvement. The findings reveal that healthcare workers are exposed to diverse hazards, including needle-stick injuries, blood-borne infections, chemical exposures, and psychosocial stress. Key weaknesses include inadequate waste segregation, inconsistent supply of personal protective equipment (PPE), and insufficient training. These challenges mirror patterns across sub-Saharan Africa, where limited resources and weak policy enforcement heighten occupational risks. While Rwanda has established strong policy commitments, implementation gaps persist. Addressing these requires reinforcing waste segregation systems, ensuring reliable PPE provision, expanding staff training, and embedding a culture of safety. Strengthening these measures is essential not only to protect healthcare workers but also to advance sustainable healthcare waste management in similar contexts globally.